Leveraging technology to improve safety on construction sites - Jenuwa, Norsyazwana; Yusop, Norhafizah Yusop; Ali, Suhaila; Wan Ismail, Wan Norizan; Mat Isa, Siti Sarah (Universiti Teknologi MARA, Perlis, 2025)
The construction industry is consistently challenged by safety risks stemming from its dynamic and hazardous working environment. Common dangers such as falls, equipment-related injuries, electrical accidents, and on-site collisions necessitate the continuous improvement of safety management practices. This study explores the adoption of advanced safety technologies to mitigate these risks and enhance on-site safety performance. Utilizing a quantitative research approach, structured surveys were distributed to 274 contractors (Grades G4 to G7) operating in Perak, Malaysia—an area with a notably high incidence of construction-related accidents and fatalities. The study focuses on the implementation of technologies such as wearable devices, drones, IoT-based monitoring systems, Building Information Modelling (BIM), and augmented reality (AR). Findings indicate a positive impact of these technologies on improving safety outcomes, including real-time hazard identification and enhanced compliance with safety regulations. However, several barriers to adoption were identified, including high costs, insufficient technical knowledge, organizational resistance, and infrastructure limitations. Statistical analysis conducted using SPSS demonstrated strong correlations between the use of specific technologies and a decrease in reported safety incidents. The study recommends increasing access to technical training, promoting affordable innovations, and developing supportive regulatory frameworks to accelerate the integration of safety technologies in the construction sector. The research underscores the critical role of technology in fostering a safer, smarter, and more resilient construction industry.